Soil erosion-reducing efficiency of litter cover varies with litter shape and coverage in a desert ecosystem. (January 2022) - Wang, Shengqi; Baima, Gaweng; Ge, Jianzhen; Fu, Wenhui; Lin, Baojun; Zhao, Shuai; Tao, Runyu; Qiao, Qianluo; Guo, Liang; Kou, Jiancun
Abstract: Wind erosion happens frequently in winter and spring, when vegetation is bare and the surface soil is prone to erosion. Therefore, the erosion resistance provided by litter is important. To investigate the soil erosion-reducing efficiency of different types of litter, litter-covered sites of Populus simonii (LPS), Caragana korshinskii (LCK) and Bothriochloa ischaemum (LBI) were studied, respectively, and bare sandy land (BSL) was taken as a control. Results showed that litter cover increased the aerodynamic roughness by 44.9%–107.1% and the friction velocity by 11.5%–52.0%. Under the conditions of fixed coverage, changing wind speed and conditions of fixed wind speed, changing coverage, the average soil erosion-reducing efficiency both showed the highest in LBI, followed by LCK and LPS. According to the trend analysis, the critical coverage of litter of Populus simonii (PS), Caragana korshinskii (CK) and Bothriochloa ischaemum (BI) to reduce the soil erosion were 8.7%, 8.2% and 9.1%, respectively. We concluded that the soil erosion-reducing efficiency varied due to the shape of litter, and the difference was significant at high wind speed (10 m s −1 and 12 m s −1 ). Besides, not all litter cover was effective in reducing erosion, and the critical coverage was a crucial factor that cannot be ignored. Highlights: When the coverage of litter was fixed and the wind speed was adjusted, the erosion reduction efficiencies were 49.1% 96.6%. When the wind speed was fixed and the coverage of litter was changed, the wind erosion reduction efficiencies were –10.2% 80.6%. According to the trend, the critical coverage of litter to reduce soil erosion were 8.2% 9.1%. The erosion reduction effect caused by the difference in the shape of litter was particularly obvious at high wind speeds. The wind erosion reduction efficiency showed that litter-covered sites of BI > CK > PS.